Explanation:
Y - intercept = (0 , -4)
X - intercept = (4/3 , 0)
You only need these two points and then you get a linear function.
First to find y-intercept, the (x) value has to be 0. So substitute 0 for (x).
You get 3-6(0)+2y=-5
now solve that. you get 3-0+2y=-5
= 3+2y=-5
= 2y = -8
= y = -4
Knowing that y = -4, x = 0. You have a point now. (0 , -4 )
Do the same for x - intercept, but this time (y) = 0. So you would get
3 - 6x + 2(0) = -5
= 3 - 6x + 0 = -5
= 3 - 6x = -5
= -6x = -8
= x = 8/6
which is app = to 4/3